Preliminary evaluation of usefulness of Habib thermoresection in treatment of parenchymal organ tumours - Tenderenda, Michał; Biernacki, Maciej; Masłowski, Zbigniew; Godlewski, Janusz; Snarska, Jadwiga (Contemporary Oncology/Współczesna Onkologia, 2009)
Aim of the study: This study was performed in order to evaluate the clinical usefulness of the Habib procedure in parenchymal organ tumour treatment. Material and methods: On 7 February, 2008, we began in our centre to use Habib’s thermoresection of such tumours. During the last eight months we have performed 5 kidney and 3 liver thermoresections. Rita generator and Habib 4X electrodes were used. Results: Surgery duration and postoperative period were shorter. In one case intraoperative transfusion was needed. Post-operative complications were not observed. Conclusions: 1. In our opinion Habib’s thermo-resection seems to be a fast, safe, effective and thus very useful technique in kidney and liver tumours’ treatment because of: • very effective bleeding protection during cutting of parenchyma, • much shorter surgery duration, • lower risk of complications (haemo-rrhage, bile leakage, infections, reoperations, kidney insufficiency or necessity of dialysis etc.). 2. We expect that this technique will spread in the nearest future. 3. Habib’s resection can be used in laparoscopy as well (using special longer type of electrodes). 4. Moreover, in small kidney tumours this procedure may allow one to avoid radical nephrectomy in selected cases.